Increase in the incidence of severe hypoglycaemia in people with Type 2 diabetes in spite of new drugs: analysis based on health insurance data from Germany. Issue 9 (12th July 2017) - Müller, N.; Lehmann, T.; Gerste, B.; Adler, J.‐B.; Kloos, C.; Hartmann, M.; Kramer, G.; Kuniss, N.; Müller, U. A.
Abstract: Aim: To evaluate the use of new anti‐hyperglycaemic agents that offer effective glycaemic control while reducing risk of hypoglycaemia, by analysing the incidence rates of severe hypoglycaemia in 2006 vs 2011 in relation to the medication. Methods: This cross‐sectional, population‐based study used German health insurance data. All adults diagnosed with Type 2 diabetes mellitus (extrapolated to the German population: 6.35 million in 2006 and 7.52 million in 2011) were screened for severe hypoglycaemia. Anti‐hyperglycaemic agents were identified by their Anatomical Therapeutic Chemical code, and defined daily doses of each medication were calculated. Results: The severe hypoglycaemic event rate was 460 per 100, 000 people/year in 2006 and 490 per 100, 000 people/year in 2011. In 2006 and 2011, 10.9% and 7.3%, respectively, of all people with severe hypoglycaemia were on sulfonylureas, while 12.7% and 9.3%, respectively, were on a combination therapy of metformin and sulfonylureas. Among those with severe hypoglycaemia, there were no prescriptions of dipeptidyl peptidase‐4 inhibitors or glucagon‐like peptide‐1 receptor agonists in 2006, but in 2011, 1.55% and 0.17%, of those with severe hypoglycaemia were receiving the respective treatments. In 2006 vs 2011, human insulin was prescribed for 11.3% vs 10.3% of people with severe hypoglycaemia, while insulin analogues were prescribed for 5.4% vs 8.1%, and mixed human insulins for 19.7% vs 14.0% of patients with severe hypoglycaemia. People receiving insulin analogue therapy had a higher risk of severe hypoglycaemia than those receiving metformin, after adjusting for age, gender, nephropathy diagnosis and year of survey (odds ratio 14.6; CI 13.3–15.9). Conclusion: The incidence of severe hypoglycaemic events in Germany increased between 2006 and 2011, despite increased use of newer anti‐hyperglycaemic agents and decreased use of insulins. What's new?: In a large cohort of people with Type 2 diabetes, we compare the incidence of severe hypoglycaemia in 2006 with that in 2011 with regard to the anti‐hyperglycaemic medication prescribed before the severe hypoglycaemic event. As expected, large increases in the use of modern anti‐hyperglycaemic agents with a supposedly lower risk of hypoglycaemia were observed in association with a significant increase in the incidence of severe hypoglycaemia between 2006 and 2011. People treated with insulin analogues compared with those treated with metformin had a higher risk of severe hypoglycaemia, with adjustment for age, sex, nephropathy diagnosis and year.